Ảnh hưởng của công nghệ tài chính và chất lượng quản trị quốc gia đến hiệu quả ngân hàng tại các nước Đông Nam Á - Hoàng Mai, Phương; Đoàn Anh, Tuấn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This paper examines how financial technology (FinTech) influences the performance of 214 commercial banks across five Southeast Asian countries between 2010 and 2023, with a particular emphasis on the moderating role of national governance quality. Using Pooled OLS and GMM estimations, the results indicate that an increase in FinTech development is associated with lower bank profitability, especially among smaller banks, due to intensified market competition. Nevertheless, FinTech development helps reduce non-performing loan ratios by expanding credit access to lower-risk customer segments. Moreover, the study finds that the beneficial impact of FinTech on bank performance is significantly stronger in countries with higher governance quality. These results remain robust after accounting for dynamic endogeneity within the FinTech – bank performance nexus.